A Systematic Review of Studies Using the Brief COPE: Religious Coping in Factor Analyses - Krägeloh, CU (MDPI Publishing, 2011)
Religion is generally recognized as a major resource for dealing with stressful events, but its relationship with secular coping strategies continues to be debated. The present article provides a systematic review of the way in which analyses of the sub-scale turning to religion of the widely used Brief COPE [1] instrument are presented in peer-reviewed research articles, in order to investigate how the wealth of data published using this instrument can inform how religious coping relates to other coping strategies. Of the 212 identified articles that included turning to religion in their analyses, 80 combined sub-scale scores to form higher-order coping factors, 38 of which based on exploratory factor analyses of their own datasets. When factor analyses had used individual items as indicators, religious coping was more likely to load together with maladaptive coping strategies, and more likely with adaptive coping strategies when analyses were conducted at sub-scale level. To a large extent, the variation in the results from exploratory factor analyses appears to be due to the diverse and often inappropriate factor analytic techniques used to determine the factor structure of the Brief COPE instrument. Reports from factor analyses of the Brief COPE therefore have very little value when trying to make general conclusions about the role of religious coping in relation to secular coping methods.
Keywords: Coping; Religion; Religious coping; Brief COPE; Systematic review